Transparency of Financial Reports and Efficiency of Digital Zakat Payments on Muzakki Decisions at Baznas Pekalongan City - Fu'aida, Taskiyatul; Titandy, Arga Dwi; Pratama, Versiandika Yudha; Elliana, Febria (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research analyzes the influence of financial report transparency and digital zakat payment efficiency on muzakki decisions at BAZNAS Pekalongan City. Using survey-based quantitative methods and Accidental Sampling techniques, 100 muzakki respondents who used digital platforms were selected. Data was collected through a four-point Likert scale questionnaire which had been tested for validity and reliability. The results show that financial report transparency has a significant influence on muzakki decisions, while digital payment efficiency does not have a partially significant effect. However, simultaneously, these two variables influence muzakki decisions with a contribution of 21.7%. This research supports legitimacy theory which emphasizes the importance of accountability and public trust in zakat management, especially in the application of digital technology. Optimizing the transparency and efficiency of digital payments in an integrated manner can increase muzakki participation and trust in zakat management institutions, relevant in the rapidly developing digital era.